ECONOMIC INEQUALITY: A SURVEY OF RECENT LITERATURE - Kulikauskas, Darius (Ekonomika, 2013)
Abstract. The purpose of this paper is to review the recent literature on economic inequality. In particular, the developments in the fields of economic growth, financial crises, happiness and skill (capital) biased technological progress are surveyed. By using the methods of systematic and narrative literature review and conducting meta-synthesis of the recent studies, it is shows that conventional wisdom is contested in all of the mentioned fields. The rising economic inequality is linked to financial crises as well as the slower and shorter economic growth. The Easterlin paradox is losing support. Skill-biased technological progress is possibly evolved into a capital-biased one. Key words: economic inequality, financial crises, skill-biased productivity, capital-biased productivity, the Easterlin paradox